Turbulencias en el clima de opinión: Aplicaciones Metodológicas de la Teoría de la Espiral del Silencio - NOELLE-NEUMANN, Elisabeth (CIC. Cuadernos de Información y Comunicación, 2010)
New tools for measuring changes in public opinion can be derived from the theory of the spiral of silence. Measures of individual assessment of the climate of opinion and of confidence about showing one’s own opinion document the processes by which the losing side falls increasingly silent and the winning side is therefore overrated.
Keywords: Theory of the Spiral of Silence; Public opinion; Opinion’ s clima; Politics; Society